2017
DOI: 10.1177/1750698017709869
|View full text |Cite
|
Sign up to set email alerts
|

The Romanian “Latchkey Generation” writes back: Memory genres of post-communism on Facebook

Abstract: Since the 2000s an alternative engagement with the communist past has emerged across media in Romania in the shape of a generational discourse, which negotiates a post-communist generational identity for individuals growing up in the 1970s-1980s. This article focuses on the online memory practices of this self-dubbed "latchkey generation" by investigating an emerging life writing genre-the Facebook generatiography-and its reliance on the archiving of communist memorabilia in the shape of photographed objects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Generational units, he argues, can also produce a bonding memory that establishes trust and reciprocal responsibilities across generations. Other studies show that cross-generational exchange of unifying memories materializes at sites of memory such as museums (Kantola, 2014) as well as social media networks (Pohrib, 2019), fostering communicative memory) Assmann, 2008). In these intergenerational encounters, memory carriers play a salient role in the production of continuity.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Generational units, he argues, can also produce a bonding memory that establishes trust and reciprocal responsibilities across generations. Other studies show that cross-generational exchange of unifying memories materializes at sites of memory such as museums (Kantola, 2014) as well as social media networks (Pohrib, 2019), fostering communicative memory) Assmann, 2008). In these intergenerational encounters, memory carriers play a salient role in the production of continuity.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Given the circumstances, the works dedicated to the memory of communism among the young generation occupy pride of place, which is a topic developed mainly after 2010 [22][23][24][25][26][27][28][29][30]. Communism in Romania was also described for young people also in a broader context, that of "illustrated stories" [31,32], etc.…”
Section: Literaturementioning
confidence: 99%
“…The overall understanding of the communist themed clubbing phenomenon may also be correlated with a particular news framing editorial peak of 2010, where the media coverage of public opinion polls conducted that year made the news with a paradoxical social trend: Romanians' nostalgia for communism ( Bardan 2020). Last, but not least, and within a larger time span, the "socialist" aspect of clubbing posters may be related to the spread of (online) alternative memory practices in a new digital and generational context (Bardan and Vasilendiuc 2019;Petrescu 2017;Pohrib 2017). The second weaker wave, which is also signaling a start in the decline of this marketing practice, may be related to similar trends identified for other Eastern European countries in studies accounting for the progressive waning of the nostalgia industry and the marketing of socialist memorabilia (Bach 2015: 125;Nadkarni and Shevchenko 2015;89).…”
Section: Retrofi Tted Visual Patternsmentioning
confidence: 99%
“…In this framework, a particular generational span is put under scrutiny in Romanian scholarly literature, namely (still) young people who came of age around the 1990s, in a context marked by acute changes, both socio-political and technological. The multi-layered online memory discourse of this liminal generation found its place rather in the growing body of alternative remembrance practices, whether it reflected the harmonization of the "latchkey" generation's identity (Pohrib 2017) or conveyed a complementary view of the past, triggered by the digital memories of an analog childhood (Petrescu 2017;. A more extensive look into how online social networks (re)mediate postsocialist memories showed that different digital communities participate in shaping polarized narratives of the past (Bardan and Vasilendiuc 2019).…”
Section: The Commodifi Cation Of the Socialist Past: The (Online) Nos...mentioning
confidence: 99%